Spin-dependent Seebeck Effect, Thermal Colossal Magnetoresistance and Negative Differential Thermoelectric Resistance in Zigzag Silicene Nanoribbon Heterojunciton - Fu, Hua-Hua (Nature Publishing Group, 2015)
Spin-dependent Seebeck effect (SDSE) is one of hot topics in spin caloritronics, which examine the relationships between spin and heat transport in materials. Meanwhile, it is still a huge challenge to obtain thermally induced spin current nearly without thermal electron current. Here, we construct a hydrogen-terminated zigzag silicene nanoribbon heterojunction, and find that by applying a temperature difference between the source and the drain, spin-up and spin-down currents are generated and flow in opposite directions with nearly equal magnitudes, indicating that the thermal spin current dominates the carrier transport while the thermal electron current is much suppressed. By modulating the temperature, a pure thermal spin current can be achieved. Moreover, a thermoelectric rectifier and a negative differential thermoelectric resistance can be obtained in the thermal electron current. Through the analysis of the spin-dependent transport characteristics, a phase diagram containing various spin caloritronic phenomena is provided. In addition, a thermal magnetoresistance, which can reach infinity, is also obtained. Our results put forward an effective route to obtain a spin caloritronic material which can be applied in future low-power-consumption technology.